A Qualitative Study of Knowledge Exchange in an Indonesian Machine-Making Company - Handoko, Indria (International Research Journal of Business Studies, 2016)
In a supply chain, company’s ability to leverage knowledge that resides within the network of contracted and interacting firms is able to improve not only company performance but also the supply chain effectiveness as a whole. However, existing supply chain studies mostly discuss knowledge at company level, and rarely at internal-hierarchical levels. As a result, many things remain concealed, for example, how knowledge exchange between people across levels in a supply chain is influenced by the supply chain government. Moreover, most exsisting studies focus on a rigid hierarchical supply-chain mechanism, and hardly elaborate how interactions in a less-rigid mechanism. This article attempts to address these gaps, discussing how a supplier company that deals with innovation generation activities acquires knowledge that resides in its supply chain network. A qualitative case study about an Indonesian machine-making company has been chosen to represent one of supplier types in the automotive industry that deals with less-rigid mechanism. A social capital perspective is applied to shed light on how interactions between actors in a supply chain network influence knowledge exchange. The study finds out a positive relationship between social capital and knowledge exchange across levels and functions to help generate innovations, allowing the company to manage conflicting effect beliefs more effectively. The study also identifies a tendency of the company to regard intensive knowledge exchange as part of organizational learning process.